Evaluating the best empirical antibiotic therapy in patients with acute-on-chronic liver failure and spontaneous bacterial peritonitis. Issue 9 (September 2019) - Wieser, Andreas; Li, Hanwei; Zhang, Jiang; Liss, Ingrid; Markwardt, Daniel; Hornung, Roman; Suerbaum, Sebastian; Mayerle, Julia; Gerbes, Alexander L.; Steib, Christian J.
Abstract: Background/aims: Spontaneous bacterial peritonitis (SBP) is a life-threatening complication of advanced cirrhosis. By studying the susceptibility of isolated organisms and analyzing empirical antibiotic therapy combined with clinical outcomes, we aimed to find an improved empirical antibiotic therapy by considering the individual acute-on-chronic liver failure (ACLF) grade for patients with or without sepsis. Methods: Clinical outcomes of 182 patients were assessed retrospectively with multivariable regression analysis. Each of the 223 isolates was individually evaluated regarding susceptibility results and intrinsic resistances. Results: Piperacillin/tazobactam had the highest antimicrobial susceptibility among monotherapies/fixed combinations, which was significantly lower than combination therapies such as meropenem-linezolid (75.3% vs. 98.5%, P < 0.001). The sensitivity of pathogens to empirical antibiotic therapy correlated with significantly lower inpatient mortality (18.9% vs. 37.0%, P = 0.018), shorter inpatient stay (16.3 ± 10.2 vs. 26.4 ± 21.0 days, P = 0.053) and shorter intensive care treatment (2.1 ± 4.5 vs. 7.9 ± 15.4 days, P = 0.016). The largest difference of mortality was observed in patients with ACLF grade 3 (54.5% vs. 73.1% [sensitive vs. non-sensitive]). Conclusion: All SBP patients benefited from efficient empirical antibiotic therapy, regarding the reduced inpatient mortality and complications. For SBP patients with ACLF grade 3 without sepsis, the combination therapy with meropenem-linezolid may be suitable considering the susceptibility results and the concentration in the peritoneal cavity.